Integrated Metabolomics and Lipidomics Analysis Reveals the Mechanism Behind the Action of Chiglitazar on the Protection Against Sepsis-Induced Acute Lung Injury - Liu-Liu Lu; Yu-Li Cao; Zhen-Chen Lu; Han Wu; Shan-Song Hu; Bing-Qing Ye; Jin-Zhi He; Lei Di; Xu-Lin Chen; Zhi-Cheng Liu (Metabolites)
Background: Sepsis-induced acute lung injury (SALI) is a critical clinical challenge with high mortality. Metabolic dysregulation drives SALI pathogenesis, disrupting lung function and energy metabolism. Despite proven benefits, metabolic restoration is underused in sepsis. This study explores chiglitazar’s role in balancing metabolism to protect against SALI. Methods: The protective effects of chiglitazar in CLP rats were demonstrated by the survival curve, histological analysis, and immunohistochemical analysis in the lung tissue. Metabolomic and lipidomic analyses of lung tissue samples using gas chromatography–mass spectrometry (GC-MS) and liquid chromatography–mass spectrometry (LC-MS) were performed to evaluate metabolic shifts induced by CLP surgery and chiglitazar pretreatment. The mRNA and protein levels of the underlying targets directing nicotinamide adenine dinucleotide (NAD+) and triglyceride synthesis were analyzed by qPCR and Western blotting. To validate the mechanism by which chiglitazar protected against SALI, the SIRT1 inhibitor EX-527 was applied to human normal lung epithelial (BEAS-2B) cells and another batch of rats to observe its reverse effect against chiglitazar’s action. Results: Chiglitazar pretreatment significantly restored NAD+ and improved dysregulated lipid metabolism by enhancing the synthesis of triglycerides (TGs) and suppressing accumulated fatty acids (FAs). The metabolic modulation mediated by chiglitazar was associated with the upregulations of the SIRT1/PGC-1α/PPARα/GPAT3 axis. Co-treatment with EX-527 in LPS-stimulated BEAS-2B cells and CLP rats inhibited the effects of chiglitazar on the aforementioned signaling pathways and worsened the protective effects of chiglitazar on lung injury, respectively. Conclusions: Chiglitazar alleviates SALI by restoring NAD+ and TG synthesis, highlighting the balancing of metabolism as a promising therapeutic strategy in the management of SALI.